Ionically Crosslinked Complex Gels Loaded with Oleic Acid-Containing Vesicles for Transdermal Drug Delivery - Wing-Fu Lai; Ryan Tang; Wing-Tak Wong (MDPI AG, 2020)
Skin is an attractive site for drug administration partly because of its easy accessibility and favorable properties (e.g., less invasiveness and high patient compliance) over some other common routes of administration. Despite this, the efficiency in transdermal drug delivery has been largely limited by poor skin permeation. To address this problem, this study reports the generation of oleic acid-containing vesicles, which can enhance the drug delivery efficiency while showing good stability and limited skin disruption. Upon being loaded into a complex gel, along with the incorporation of the polymer blending technique, a delivery system exhibiting tunable transdermal flux of 2,3,5,4'-tetrahydroxystilbene 2-O-β-D-glucoside is reported. Taking the good biocompatibility and tunable delivery performance into account, our system warrants further development and optimization for future applications in the treatment of skin diseases.